Bio-priming with salt tolerant endophytes improved crop tolerance to salt stress via modulating photosystem II and antioxidant activities in a sub-optimal environment - Irshad, Khadija; Shaheed Siddiqui, Zamin; Chen, Jianjun; Rao, Yamna; Hamna Ansari, Hafiza; Wajid, Danish; Nida, Komal; Wei, Xiangying (Frontiers in Plant Science, 2023)
The sustainability of bio-priming with salt tolerant endophytes modulated plant photo-physiology; light harvesting efficiency, quantum fluxes, and antioxidant functionality in a sub-optimal environment were conducted. Salt tolerant Paecilomyces lilacinus KUCC-244 and Trichoderma hamatum Th-16 was obtained. Later, the endophytes were cultured on different NaCl containing PDA mediums. The highest salt (500mM) tolerant fungal colonies were selected and purified. The selected 61.3×10-6 conidia /ml of Paecilomyces and about 64.9× 10-3 conidia / ml of Trichoderma colony forming unit (CFU) were used for priming. Twenty- days-old primed and unprimed seedlings were subjected to 100 and 200 mM NaCl. Wheat and Mung bean were allowed to grow at an average day-night temperature of 33 ± 4 ºC to 22 ± 3 ºC. T. hamatum significantly increased the growth, chlorophyll content, and stomatal conductance over unprimed control under extreme salt stress. In the current investigation, we discovered that stress markers like H2O2 and MDA were decreased by bio-priming in a sub-optimal environment. However, in wheat plants, the level of H2O2 was considerably lower than in mung bean plants. Moreover, the quantum yield (FV/FM) and PSII efficiency of bio-priming treated stressed plants over control were enhanced. These outcomes are suggestive that T. hamatum had greater efficacy in enhancing salt tolerance, which is linked with the improved PSII functionality in stressed plants. Further, bio-primed plants had considerably less energy loss corresponding with lower damage at PSII level. The OJIP curve of the present work showed a decrease in I and P values with the increase in salt stress. The increase in I and P steps in T. hamatum and P. lilacinus primed plants showed the availability of more active reaction centers (RC) PSII under salt stress in comparison to unprimed control plants. This indicated that bio-primed plants were more tolerant to salt stress. The infrared thermographic images also substantiated the findings.